Hubungan Pola Komunikasi Authoritative Orang Tua Dengan Kepercayaan Diri Anak Usia Dini Di Nagari Koto Baru Kabupaten Padang Pariaman - Belia, Belia Amanda; Natsir, MHD (Jurnal Family Education, 2024)
Low level of self-confidence, and parents have less time with their children, so there is rarely communication between children and their parents.The purpose of the research activity is to find out the description: authoritative communication patterns of parents, self-confidence of children aged 4-6 years, and the relationship between parents' authoritative communication patterns and children's self-confidence age 4-6 years in Nagari Koto Baru, Padang Pariaman Regency. The research was conducted using a quantitative approach with the type of correlation type. The study population is parents who have children aged 4-6 years in Nagari Koto Baru, Padang Pariaman Regency. The research sample was taken with area random sampling technique. Research instruments in collecting data using a questionnaire. The data analysis technique uses percentage formula and product moment. The results of the study indicate that: (1) Authoritative communication patterns are categorized as not good; (2) Self-confidence of children aged 4-6 years is categorized as low, and (3) There is a very significant relationship between authoritative communication patterns of parents with early childhood self-confidence in Nagari Koto Baru Padang Pariaman Regency.